A Method to Assess Neurological Effectiveness of a Spinal Adjustment for an Individual Patient: A Descriptive Study - Hart, John (International Journal of Statistics in Medical Research, 2016)
Introduction: A hallmark in health care research is comparison, typically done by comparing groups of patients, e.g., intervention group versus no intervention group. The clinician may be interested in bringing these research methods to the level of the individual patient in practice. Such is done in the present study, where the neurological indicator of resting pulse rate (RPR) is compared pre versus post spinal adjustment, and also compared to instances of no adjustment – for one individual patient. Research indicates that a lower RPR is healthier than a higher RPR. Methods: Neurological disturbance was operationally defined in the present study as at least two increases in RPR on consecutive visits. Based on this criterion, the patient, over hundreds of RPR measures observed over approximately 2 years, had 16 instances of neurological disturbance; in one of these instances a chiropractic spinal adjustment was given. The 15 other instances were used to estimate a predicted post RPR, which was compared to the observed post-adjustment RPR. Results: Post-adjustment RPR was 67.5 beats per minute (BPM) which was only slightly lower than the average predicted post RPR of 68.1 BPM. Conclusion: The method described may help clinicians determine if their intervention was neurologically effective. The method also provides normative RPR data for future comparisons of adjustment versus no adjustment. In the present case, the chiropractic adjustment post RPR was better (lower) than the predicted post RPR, but only slightly so.